Exploring the experiences of persons with mobility impairments in accessing health care in Cofimvaba, South Africa - Tshaka, Babalwa Blossom (Stellenbosch : Stellenbosch University, 2021)
Thesis (MHumanRehabSt)--Stellenbosch University, 2021.